Recalibrating Public Service: Valuing Engagement, Empathy, Social Equity, and Ethics in Public Administration. (3rd September 2022) - Dolamore, Stephanie; Whitebread, Geoffrey
Abstract: Public administrators are not neutral actors. Their work occurs in the context of historical and contemporary systemic oppression. Yet, the traditional values that guide the field, efficiency, effectiveness, and economy, are not responsive to this context. This article proposes a recalibrated set of values to support the process and outcomes of public administration to address systemic oppression more sufficiently. Drawing on interviews conducted with American Sign Language interpreters, findings explore the role of engagement, empathy, equity, and ethics in the delivery of public services to the Deaf community. This work includes a call to action for more research on the recalibrated "4Es" and the establishment of a code of professional conduct for the field of public administration.